2016
DOI: 10.1097/prs.0000000000002271
|View full text |Cite
|
Sign up to set email alerts
|

Mid-Term Dental and Nerve-Related Complications of Infant Distraction for Robin Sequence

Abstract: Therapeutic, IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 30 publications
2
53
0
Order By: Relevance
“…One potential benefit of VSP is the avoidance of damage to developing dental structures. In a series of 85 patients who underwent MDO in infancy and had a median follow-up of 7.3 years, Steinberg et al found that 47.7% had abnormal formation of the permanent mandibular first molar tooth, and the primary mandibular second molar was injured in 13.6% 1 . The ability to modify these outcomes by 3D visualization of the developing dentition and customization of osteotomy designs, however, is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One potential benefit of VSP is the avoidance of damage to developing dental structures. In a series of 85 patients who underwent MDO in infancy and had a median follow-up of 7.3 years, Steinberg et al found that 47.7% had abnormal formation of the permanent mandibular first molar tooth, and the primary mandibular second molar was injured in 13.6% 1 . The ability to modify these outcomes by 3D visualization of the developing dentition and customization of osteotomy designs, however, is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Mandibular distraction osteogenesis (MDO) has become the first-line operation in many centers for infants with airway obstruction associated with (Pierre) Robin sequence (RS) who have failed non-invasive management 1 . This procedure boasts high rates for successful resolution of obstructive sleep apnea (OSA) and avoid-ance of tracheostomy [2][3][4][5][6][7][8][9][10][11][12] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Premolars were the second most commonly absent teeth in this study, which is again consistent with prior reports. 12,13 Other major molar abnormalities at the permanent dentition phase included dysplasia, impaction, ectopia, and ankylosis of multiple teeth, including the canine, premolars, and molars. Canines and premolars were impacted at higher rates than would be expected in the general population.…”
Section: Face 2(3)mentioning
confidence: 99%
“…Mandibular distraction osteogenesis (MDO) is commonly used to relieve retroglossal airway obstruction in infants with Robin sequence (RS). 1 Virtual surgical planning (VSP) may aid in device selection and placement, facilitate vector management, simplify the operation, improve precision, and decrease complications such as damage to adjacent developing teeth and nerves. 2 This report describes an algorithm for VSP and three-dimensional (3D) printing of cutting guides for MDO in infants with RS.…”
Section: Introductionmentioning
confidence: 99%